Martin Marprelate and the Popular Voice - Cummings, Brian ca. 20./21. Jh. (Studies in church history, 2006)
The curious career of ‘Martin Marprelate, gentleman’ is one of the most notorious and at the same time elusive episodes in the history of English puritanism, inspiring endless if largely futile speculation into the identity of its author. Part literary canard, part political scandal, part detective story, for around a calendar year between October 1588 and September 1589, Martin and his associates kept one step ahead of the pursuivants and produced seven scurrilous tracts aimed at the ecclesiastical hierarchy. Adding spice to the story, their main targets, John Whitgift, archbishop of Canterbury, and John Aylmer, bishop of London, were also the officers empowered by the Star Chamber in 1586 both to examine religious dissidents and to supervise the press. To keep up his cottage industry of satire and vilification, Marprelate moved his printing press from county to county (from Surrey to Northamptonshire to Warwickshire to Lancashire), from private dwelling to private dwelling, and turned the failure of his pursuers into further occasion for ridicule, insult, and his own popular triumph over adversity. Like a will o’ the wisp, he could disappear into the bushes and then emerge in a printed book whenever he wanted. Even after the main part of the operation was broken up and the typeface destroyed, he managed to get out one final tractlet as a last snook at the authorities. And then, whereas the printmen were examined and tortured, and Whitgift went after the more serious elements of the presbyterian cause with relentless violence, Martin himself escaped entirely.